A New Type of Congenital Dysfibrinogen, Fibrinogen Bremen, with an Aα Gly-17 to Val Substitution Associated with Hemorrhagic Diathesis and Delayed Wound Healing - Wada, Yasuo; Niwa, Kazuki; Meakawa, Hisato; Asakura, Shinji; Sugo, Teruko; Nakanishi, Makoto; Auerswald, Günter; Popp, Manfred; Matsuda, Michio (Thrombosis and Haemostasis, 1993)
We have identified a new type of Aα Gly-17 to Val substitution in a congenital dysfibrinogen, fibrinogen Bremen, derived from a 15-year-old boy having manifested easy bruising and delayed wound healing. The functional abnormality was characterized by altered fibrin monomer polymerization, which became evident by increasing the salt concentration and pH. A synthetic tetrapeptide with a sequence of the amino-terminal segment of normal fibrin α-chain, Gly-Pro-Arg-Val, substantially inhibited polymerization of both normal and the patient-derived fibrin monomers. A synthetic tetrapeptide with the Bremen type sequence of Val-Pro-Arg-Val inhibited polymerization of the patient’s fibrin monomers partially at a peptide: fibrin monomer molar ratio of 4,000:1, and that of normal one at a much higher ratio of 10,000:1. Likewise, a synthetic peptide Ala-Pro-Arg-Val with a replacement of the Gly residue by another aliphatic amino acid Ala inhibited similarly the patient’s fibrin monomer polymerization. Thus, the hypothetical two-pronged socket-like structure consisting of the α-amino group of the amino-terminal Gly and the guanidino group of an Arg at position 3 of the normal fibrin α-chain seems to be restored considerably in the mutant fibrin α-chain at low ionic strengths and pH’s, despite the replacement of the amino-terminal Gly by another aliphatic amino acid Val.